Nicotinamide riboside supplementation ameliorates ovarian dysfunction in a PCOS mouse model - Zhenye Zhu; Min Lei; Ruizhi Guo; Yining Xu; Yanqing Zhao; Chenlu Wei; Qingling Yang; Yingpu Sun (Journal of Ovarian Research)
Abstract Polycystic ovary syndrome (PCOS) is the leading cause of anovulatory infertility among women of reproductive age, yet the range of effective treatment options remains limited. Our previous study revealed that reduced levels of nicotinamide adenine dinucleotide (NAD+) in ovarian granulosa cells (GCs) of women with PCOS resulted in the accumulation of reactive oxygen species (ROS) and mitochondrial dysfunction. However, it is still uncertain whether increasing NAD+ levels in the ovaries could improve ovarian function in PCOS. In this study, we demonstrated that supplementation with the NAD+ precursor nicotinamide riboside (NR) prevented the decrease in ovarian NAD+ levels, normalized estrous cycle irregularities, and enhanced ovulation potential in dehydroepiandrosterone (DHEA)-induced PCOS mice. Moreover, NR supplementation alleviated ovarian fibrosis and enhanced mitochondrial function in ovarian stromal cells of PCOS mice. Furthermore, NR supplementation improved oocyte quality in PCOS mice, as evidenced by reduced abnormal mitochondrial clustering, enhanced mitochondrial membrane potential, decreased ROS levels, reduced spindle abnormality rates, and increased early embryonic development potential in fertilized oocytes. These findings suggest that supplementing with NAD+ precursors could be a promising therapeutic strategy for addressing ovarian infertility associated with PCOS. Graphical Abstract Ovarian NAD+ levels decreased in DHEA-induced PCOS mice, accompanied by mitochondrial dysfunction in oocytes and ovarian stromal cells, resulting in reduced oocyte quantity and quality, decreased early embryonic development potential, and increased ovarian fibrosis. After increasing ovarian NAD+ levels by NR supplementation to restore PCOS-related impairment of mitochondria function, ovarian dysfunction in PCOS was attenuated as characterized by improved oocyte quantity and quality, enhanced early embryonic development potential, and decreased ovarian fibrosis.